ANALYSIS OF INSULT AS HUMOR IN THE CONTEXT OF POLITICS THROUGH STAND-UP COMEDY SHOW - Reski Kartini Addas (Journal of Language, Literature and Teaching, 2022)
This research explains the humor styles used in the stand-up comedy show by Kiki Saputri. She owns material that is known as "Roast." It is used for a specific person on the show. A roast consists of an insult, which is the background of this research. This kind of comedy can be found on TV programs or Youtube videos that contain comedy content because they get special attention from the viewers. Besides that, many films featured comedians, particularly stand-up comedians. They can use comedy to not only make people laugh but also to criticize, deliver messages, and capitalize on unrest. In this research, the researcher used descriptive qualitative research as the method of the research. The analysis used the theory of Arthur Asa Berger. In this theory, Berger said that there are 45 indicators of humor, but the researcher just used insult as one indicator to focus on this research. The researcher wants to analyze the use of insults in the Roast Stand Up Comedy Show in a political context from Youtube. The research results show that using insults can be humorous because it can make the audience laugh. Furthermore, the show was served in good humor but not for serious insults in front of politicians. Thus, they not only entertain the audience but also deliver messages or criticism directly to the politicians.  Keywords: Humor, Roast, Insult, Comedian, Politician.